Firebrand Generation Rates at the Source for Trees and a Shrub - Adusumilli, Sampath; Chaplen, James E.; Blunck, David L. (Frontiers in Mechanical Engineering, 2021)
Source terms of the number of firebrands released as trees/shrubs torch are essential for helping to more accurately implement detailed physics-based models of wildfire propagation, particularly when torching occurs. A key challenge in estimating these source terms is the difficulty in measuring firebrand generation rates from the source. Typical studies have reported generation characteristics (firebrands/m2), but enumeration of the total number of firebrands released has remained elusive. Recently, a fire-resistant fabric was successfully employed to quantify “hot” firebrands (i.e., can potentially lead to further fire spread) generated during tree-scale burns. In this paper, a total of 71 tree/shrubs were burned to quantify hot firebrand production statistics for Douglas-fir, ponderosa pine, and sagebrush. A network of 65 fire-resistant fabric stations were deployed during the burns to measure the “hot” firebrands that are released. These stations are placed strategically at several radii and angles in the prominent wind direction. Using the number of firebrands determined from the fabric, a first-order extrapolation method was developed and evaluated to estimate the source terms (i.e., total number of hot firebrands released). Variation in the firebrand production with the height of the trees and for three species is reported. The total number of hot firebrands produced typically increased with the height of the tree/shrub burned as expected. The specific hot firebrand production (firebrands produced per kg dry mass burned) is exponentially dependent on the moisture content of the tree and had an inconclusive correlation with the height of the trees. Overall, for trees of comparable moisture content, sagebrush produced higher specific hot firebrands when compared to ponderosa pine and Douglas-fir species.